2016
DOI: 10.1298/ptr.e9884
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative gluteus medius muscle atrophy as a predictor of walking ability after total hip arthroplasty

Abstract: ABSTRACT. Purpose: To elucidate the relation between certain preoperative physical parameters and walking with a limp after total hip arthroplasty (THA) and determine whether it is possible to predict the walking ability of patients 6 months after THA. Methods: The subjects of this study comprised 74 female patients who had undergone unilateral THA. Before surgery, the hip abductor and knee extensor strengths were measured, the cross-sectional areas (CSAs) of the gluteus medius and rectus abdominis muscles wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…According to the analysis of the linear regression model, when the FO increased by 2.3–2.9 mm, the abductor and external rotator moment arms increased, and the other muscle moment arms decreased by less than 5% ( Tables 2 , 3 ). Nankaku et al (2016) have reported that an abnormal gait pattern caused by asymmetrical frontal motion was associated with muscle atrophy of the hip abductor muscle before THA. The hip abductor moment arm rising due to an FO increase following THA may compensate for abductor weakness caused by muscle atrophy, which could improve work efficiency and improve gait imbalance.…”
Section: Discussionmentioning
confidence: 99%
“…According to the analysis of the linear regression model, when the FO increased by 2.3–2.9 mm, the abductor and external rotator moment arms increased, and the other muscle moment arms decreased by less than 5% ( Tables 2 , 3 ). Nankaku et al (2016) have reported that an abnormal gait pattern caused by asymmetrical frontal motion was associated with muscle atrophy of the hip abductor muscle before THA. The hip abductor moment arm rising due to an FO increase following THA may compensate for abductor weakness caused by muscle atrophy, which could improve work efficiency and improve gait imbalance.…”
Section: Discussionmentioning
confidence: 99%
“…GMed size was smaller on the affected side in severe OA than on the contralateral side or in controls Nankaku M et al 126) Female patients with unilateral THA (n=74) Preoperative gluteus medius atrophy was correlated to limping after THA Momose T et al 127) Patients with unilateral hip OA (n=50) Hip abd. strength was correlated to HHS/CT density Hip abd.…”
Section: Discussionmentioning
confidence: 99%
“…The pre-operative strength of muscles stabilizing the pelvis during walking may be a determinant of postoperative improvement of gait function. Analogous studies have demonstrated the impact of pre-operative quadriceps strengthening on results obtained shortly after replacement [36].…”
Section: Personalization Of the Rehabilitation Programmentioning
confidence: 93%
“…Screening performed before the operation to identify people with this problem will allow personalization of the rehabilitation process, taking into account existing muscle dysfunction. This will allow the setting of training goals appropriate to the patient's needs and a more rapid improvement of gait function [36]. Pre-operative training may also strengthen the middle gluteal muscles.…”
Section: Personalization Of the Rehabilitation Programmentioning
confidence: 99%